Collaboration Between Parents and Teachers in the Formation of Students' Religious Character Through Islamic Religious Education Learning in the Era of Digitalization: A Case Study at SDIT - Shinta Novia; Edi Suresman; Cucu Surahman (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This study explores the collaborative model between teachers and parents in shaping the religious character of elementary school students in the digitalization era. The research is situated within the broader discussion of character education, which emphasizes the integration of moral values, religious practice, and family–school partnership. The purpose of this study is to examine the forms, processes, and effectiveness of collaboration between teachers and parents in strengthening students’ religious character through Islamic Religious Education (PAI) learning at SDIT Al-Maadin. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman interactive model. The findings reveal that teachers play a central role as moral role models (uswah hasanah) by integrating religious values into daily learning activities, establishing routines of prayer, Qur’an recitation, and moral habituation. Parents, on the other hand, act as partners who reinforce school-based religious practices at home through monitoring, guidance, and communication facilitated by the student handbook and WhatsApp groups. The study shows that digitalization does not require sophisticated technological tools; instead, it highlights the strategic use of simple digital communication to strengthen family–school synergy. Collaboration between teachers and parents results in the development of students’ religious character across three domains: aqidah–ibadah, moral conduct, and social values. The study concludes that consistent coordination and shared responsibility between school and family significantly enhance students’ religious character, though challenges remain in ensuring consistent home practices amid varied parenting patterns and digital distractions. Future research may examine comparative models across different school settings or explore parental digital literacy in greater depth